Pelatihan Mindfulness Berbasis Pendekatan Kognitif untuk Mengurangi Kecenderungan Alexithymia pada Mahasiswa - Nurul Azmi Arifuddin; Widyastuti Widyastuti; Ahmad Ridfah (Universitas Islam Indonesia, 2021)
Alexithymia refers to a speceofo distrubance in emotional processing that is manifested through difficulties in identifying and verbalizing feeling. this study aims to examine the effectiveness of mindfulness training based cognitive approach in reeducing alexithmia levels in college students.